Media Events, Digitalization and Criticism – A Communication Studies View of the 2022 FIFA World Cup - Nieland, Joerg Uwe Nieland; Winter, Rainer (Journal of Contemporary Issues in Media & Communication (JCIMC), 2025)
Cup and the Olympic Games, highlighting their lasting significance in communication studies. These events are seen as major social occasions that create public spaces where diverse groups converge, promoting social integration and cultural identity through shared values. They act as ritualized "high holy days of communication," fostering communal experiences that strengthen societal bonds.The rise of digital media has significantly transformed how these events are produced, distributed, and economically structured. Digitalization has broadened opportunities for public participation and extended engagement beyond the events themselves, enhancing the worldwide visibility of sport and reinforcing its dual role as a cultural phenomenon and economic force. The escalating costs of media rights have empowered international sports federations, affecting athlete pay and enabling detailed coverage across emerging formats and channels.Sporting mega-events are thus not only entertainment but also reflections of wider social dynamics, including neoliberal ideals centered on competition. They connect individuals globally through shared symbolic participation, reflecting sociological concepts of the sacred and communal ritual. Additionally, the text highlights changing journalistic practices and the tension between using sport for commercial or political ends versus its potential as a venue for protest and social critique in the digital age.